m6A-mRNA Methylation Regulates Gene Expression and Programmable m6A Modification of Cellular RNAs With CRISPR-Cas13b in Renal Cell Carcinoma - Gan, Ying; Li, Aolin; Liu, Jun; Wang, Xiaofei; Zhang, Zhenan; Li, Qinhan; Ye, Xiongjun; Yao, Lin; Zhang, Qian (Frontiers in Genetics, 2022)
Background: N6-Methyladenosine (m6A) is the most widespread internal messenger RNA modification in several species. In spite of latest advances in researching the biological roles of m6A, its function in the development and progression of renal cell carcinoma (RCC) remains unclear. Methods: In this study, we used meRIP-seq and RNA-seq methods to obtain a comprehensive transcriptome-wide m6A profiling and gene expression pattern in RCC and paired adjacent tissues. M6A methylated mRNAs were validated by RT-qPCR in tissues and targeted methylation or demethylation using a CRISPR-Cas13b-based tool in RCC cell line. Results: Our findings show that there were 13805 m6A peaks among 5568 coding gene transcripts (mRNAs) in adjacent tissues, and 24730 m6A peaks among 6866 mRNAs in tumor tissues. Furthermore, m6A is most often harbored in the coding sequence (CDS), with some near the start and stop codons. Gene ontology analysis revealed that coding genes had differentially methylated N6-methyladenosine sites and were enriched in kidney development and cancer-related signaling pathways. We also found that different levels of m6A methylation can regulate gene expression. Conclusions: In summary, our results provide an evidence for studying the potential function of RNA m6A modification and m6A-mediated gene expression regulation in human RCC.